The The identification of gram-negative bacteria and their effects on liver histopathology of Amazon Sailfin Catfish (Pterygoplichthys pardalis) in Lapompakka and Sidenreng Lakes, Wajo. - Hairul Afzan; Wa Ode Santa Monica; Andi Magfirah Satya Apada; Andi Rianti Rhasinta (Hasanuddin University, 2021)
Amazon Sailfin Catfish (Pterygoplicththys pardalis) or commonly known as Plecos is originated from Amazon River in South America Continent. The aims of this study are to identify and isolate pathogenic gram-negative bacteria in the liver of the plecos from Lapompakka and Sidenreng Lakes and to observe the histopathological changes in liver identified with gram-negative bacteria infection. 10 samples were collected from both lakes with each 5 representing each lake. Identification and Isolation of gram-negative bacteria was performed through culture of pleco's liver swab results in MacConkey media using gram staining method and were continued by biochemical testing using VITEK 2 System. The acquired results indicated that there were 8 different species of gram-negative bacteria isolated and all of them were pathogenic to the plecos. The species of bacteria includes Klebsiella pneumoniae, E.coli, proteus sp., Acinetobacter baumannii, Aeromonas sobria, Enterobacterb cloacae complex, Citrobacter freundii, Enterobacter aerogenes. Specimen preparation for liver histopathology was carried out by 10% neutral buffered formalin (NBF) fixation, graded ethanol series dehydration, paraffin wax embedding, 4 μm sectioning, Hematoxylin and Eosin Staining. After that, the specimen was observed under a microscope. Data analysis employed qualitative descriptive method. From the observation, liver damages such as necrosis, inflammatory cell infiltration, hemorrhage, and cell hyperthrophy were identified. Liver damages were most probably caused by the infection of gram-negative bacteria. Keywords : Sidenreng Lake, Lapompakka Lake, Liver, Histopathology, Amazon Sailfin Catfish